2010
DOI: 10.1007/s10646-010-0470-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-nonylphenol, fish predation and food availability on survival and life history traits of Daphnia magna straus

Abstract: This study aimed to investigate the compound effect of environmentally relevant 4-nonylphenol (NP) concentrations and natural stressors-namely fish predation and food availability-on Daphnia magna, which were exposed to four NP concentrations (0, 1, 5 and 10 microg l(-1)) under optimum or low food concentrations (1.00 and 0.075 mg C l(-1), respectively) in water (un)conditioned by a fish predator (Alburnus alburnus). A(n) "environmentally relevant" and "no observable effect" concentration (NOEC) of NP (10 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 82 publications
2
10
0
Order By: Relevance
“…We found direct effects of salinity on Plecoptera depended on biotic interactions with salt-tolerant taxa (figure 5b). Similar to the response of Plecoptera taxa that we found, Beklioglu et al [31] identified low and environmentally relevant concentrations of the organic toxicant 4-nonylphenol had no observable effects on Daphnia magna Straus in single toxicity tests with abundant food, but had strong effects when coupled with effects that might be expected in a real ecosystem (i.e. food limitation and predator cues).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found direct effects of salinity on Plecoptera depended on biotic interactions with salt-tolerant taxa (figure 5b). Similar to the response of Plecoptera taxa that we found, Beklioglu et al [31] identified low and environmentally relevant concentrations of the organic toxicant 4-nonylphenol had no observable effects on Daphnia magna Straus in single toxicity tests with abundant food, but had strong effects when coupled with effects that might be expected in a real ecosystem (i.e. food limitation and predator cues).…”
Section: Discussionsupporting
confidence: 86%
“…Standard toxicity test methods are structured to minimize control mortality and estimates of toxicity, therefore biological interactions are deliberately avoided [49]. Physical disturbance [50], food limitation [31], and chronic exposure [51], are similarly not typically considered in toxicity tests, although all influence toxicant effects [49]. There are many examples of biotic interactions influencing stressor effects, antagonistically [36], synergistically [35], through delaying recovery [19], with effects in both positive and negative directions [14,19,33,36,49,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…In toxicity studies, single-trophic level testing does not accurately predict the 'real world', which is rather complex due to the presence of biotic interactions (Cairns 1983;Beklioglu et al 2010). Additionally, in order to better understand the mechanisms affecting the organismal level, it is crucial to reveal the molecular responses of target organisms to stressors.…”
Section: Introductionmentioning
confidence: 99%
“…To keep the un‐ionized ammonia concentrations constant, the test solution in each beaker was measured and replaced with a fresh one every day. Ammonia test solutions were prepared by dissolving ammonium chloride NH 4 Cl (Sinopharm, Shanghai, China) in de‐chlorinated tap water . The experimental conditions were identical to those used for laboratory maintenance.…”
Section: Methodsmentioning
confidence: 99%